Temporal distribution of the mesozooplankton in the Muriá creek, Pará, Brazil - Leite, Natália da Rocha; Pereira, Luci Cajueiro Carneiro; Costa, Rauquírio Marinho da (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2009)
The temporal variations of the zooplanktonic community and physical and chemical water parameters were studied bimonthly between July 2003 (dry period) and May 2004 (rainy period) in the Muriá creek. Zooplankton sampling was carried out at neap tides, in daytime, using conical plankton net with 200 μm mesh size. Simultaneously, temperature,salinity and pH were measured in situ through a multiparameter probe and water samples were collected to determineconcentrations of dissolved oxygen and suspended particulate matter. It was verified a sharp temporal variation of salinity with higher values reported in the dry season. A total of 67 taxonomic groups was identified, being Arthropoda the most represented group, of which Acartia tonsa Dana, 1849 (Copepoda) had the highest densities (average values higher than 1,200 ind.m-3) recorded during the rainy period. In the dry period, Brachyura zoeae was the most abundant group presenting high density values. Water salinity influenced by rainfall, was the principal responsible for the temporal variations of the zooplankton community in Muriá creek.
Keywords: Zooplankton; Estuary; Amazon region